FDSOI and Bulk CMOS SRAM Cell Resilience to Radiation Effects. (September 2016) - Calienes Bartra, W.E.; Vladimirescu, A.; Reis, R.
Abstract: With shrinking dimensions and increased number of on-chip transistors radiation can provoke faults in integrated circuits even at sea level. This paper presents a comparison of fully depleted SOI (FDSOI) and Bulk CMOS 6T SRAM cells' resilience to radiation effects. Both cells were simulated using TCAD tools, considering heavy-ion impacts in different locations of the transistor as well as using different impact angles. Two types of radiation effects have been considered: Single-Event Transients (SETs) and Single-Event Upsets (SEUs). The minimum critical collected charge (CC) to flip a cell is almost the same in both technologies. However, it is shown that a FDSOI SRAM cell needs a heavy-ion impact with a Linear Energy Transfer (LET) around 10 times greater than a Bulk-CMOS SRAM cell, to generate a similar CC and to flip a cell. Highlights: Heavy-Ion impacts in devices with different impact angles. The Collected Charge in FDSOI device is approximately 7.2 times less than the Charge in Bulk device. A heavy ion with 10.6 times more LET is necessary to flip the FDSOI SRAM compared to that of a heavy ion flipping a Bulk SRAM.